Sudeten: Erinnerung reinterpretiert - Jan Pacholski (Góry, Literatura, Kultura)
The obelisk, placed at the corner of today’s Kościuszki and Daszyńskiego streets in Kłodzko, originally commemorated Friedrich Wilhelm von Götzen, a Prussian general and hero of the Napo leonic Wars. After World War II, this monument was reinterpreted; Borussian symbols were removed from it, including the emblematic eagle taking flight and the visage of von Götzen himself, and replaced with a hammer and sickle and a red star. As a result, it became one of many socalled monu ments of gratitude to the Red Army. After the political changes in 1989, the dilapidated obelisk, with its red with the red paint already flaking off, was covered with sheets of bluish glass with the logo of Powszechny Zakład Ubezpieczeń (the oldestt surviving Polish insurance company) attached. And thus, in a second bout of this peculiar process of upcycling, the new ultracapitalist reality of the Third Polish Republic regurgitated the former Prussian symbol, repurposing it to fit its current needs.